Prognostic Value of Modified Coronary Flow Capacity Derived From [15O]H2O Positron Emission Tomography Perfusion Imaging - de Winter Ruben W; Jukema Ruurt A; van Diemen Pepijn A; Schumacher Stefan P; Somsen Yvemarie BO; van de Hoef Tim P; van Rossum Albert C; Twisk Jos WR; Maaniitty Teemu; Knuuti Juhani; Saraste Antti; Nap Alexander; et al. (Lippincott Williams & Wilkins, 2025)
BACKGROUND
Coronary flow capacity (CFC) is a measure that integrates hyperemic myocardial blood flow and coronary flow reserve to quantify the pathophysiological impact of coronary artery disease on vasodilator capacity. This study explores the prognostic value of modified CFC derived from [15O]H2O positron emission tomography perfusion imaging.
METHODS
Quantitative rest/stress perfusion measurements were obtained from 1300 patients with known or suspected coronary artery disease. Patients were classified as having myocardial steal (n=38), severely reduced CFC (n=141), moderately reduced CFC (n=394), minimally reduced CFC (n=245), or normal flow (n=482) using previously defined thresholds. The end point was a composite of death and nonfatal myocardial infarction.
RESULTS
During a median follow-up of 5.5 (interquartile range, 3.7-7.8) years, the end point occurred in 153 (12%) patients. Myocardial steal (hazard ratio [HR], 6.70 [95% CI, 3.21-13.99]; P<0.001), severely reduced CFC (HR, 2.35 [95% CI, 1.16-4.78]; P=0.018), and moderately reduced CFC (HR, 1.95 [95% CI, 1.11-3.41]; P=0.020) were associated with worse prognosis compared with normal flow, after adjusting for clinical characteristics. Similarly, in the overall population, increased resting myocardial blood flow (HR, 3.05 [95% CI, 1.68-5.54]; P<0.001), decreased hyperemic myocardial blood flow (HR, 0.68 [95% CI, 0.52-0.90]; P=0.007) and decreased coronary flow reserve (HR, 0.55 [95% CI, 0.42-0.71]; P<0.001) were independently associated with adverse outcome. In a model adjusted for the combined use of perfusion metrics, modified CFC demonstrated independent prognostic value (overall P=0.017).
CONCLUSIONS
[15O]H2O positron emission tomography-derived resting myocardial blood flow, hyperemic myocardial blood flow, coronary flow reserve, and CFC are prognostic factors for death and nonfatal myocardial infarction in patients with known or suspected coronary artery disease. Importantly, after adjustment for clinical characteristics and the combined use of [15O]H2O positron emission tomography perfusion metrics, modified CFC remained independently associated with adverse outcome.